Instruments Supporting Creative Clusters in Poland and Europe - Olko, Sławomir (Regional Barometer. Analyses & Prognoses, 2015)
The paper presents the general analysis of exiting instruments supporting creative clusters using described information about existing public support for clusters. Instruments for supporting clusters are the direct consequence of innovation policy and cluster policy realized on the EU, national and regional level. Because its specificity creative cluster needs specific instruments of support adapted to the methods of knowledge management in the cluster and activities carried out by the cluster. In the new programming period (2014–2020) varied forms of support have been provided, involving directly and indirectly creative clusters.